PELESTARIAN DAN REVITALISASI RUMAH TRADISIONAL BATAK TOBA SEBAGAI DAYA TARIK WISATA BUDAYA DI DANAU TOBA - Lase, Apriliani; Lase, Apriliana; Tambunan, Jessica Ignatia (Kepariwisataan: Jurnal Ilmiah, 2025)
AbstractThis study aims to analyze the impact of traditional Batak Toba houses as a potential tourist attraction that is currently heading towards extinction and how the concept of preservation and revitalization is in maintaining tourist attractions. This study adopts a mixed method/combining quantitative and qualitative approaches (mix methods). Data collection techniques use in-depth interviews, questionnaires, observations, documentation studies, literature studies and online data searches. Primary data sources obtained directly from direct observation and interviews consisting of the government and private sectors (stakeholders), as well as distributing questionnaires using Google Form to 100 respondents with purposive sampling techniques and based on tourist visits who have visited the Lake Toba area based on the point of attraction of visiting, cleanliness conditions, security guarantees, satisfaction with management services, satisfaction with tourist attractions, satisfaction during tourism. The results of the study showed that tourist responses to the quality of the Traditional House tourist attraction still have a high percentage value of 60.8% and are followed by a level of satisfaction in tourism of 45.7%. However, the point of cleanliness still has a low percentage of 20.6, meaning the importance of improving cleanliness in the tourist area located in the Lake Toba area, Samosir. Good attention and cooperation from the local government to the private sector is very important to maintain and preserve buildings so as to create comfort for tourists who visit, as well as tourism awareness that is very necessary to be increased to support progress in the Lake Toba tourist area. The role of the community is also very much needed in the development of traditional house tourism objects so that they do not go extinct but this area increasingly shows its identity in its preservation and revitalization..Keywords: Traditional Batak House; Attraction; Tourist Visits; Revitalization; Lake TobaAbstrakPenelitian ini bertujuan untuk menganalisis dampak rumah adat Batak Toba sebagai potensi objek wisata yang saat ini mulai menuju kepunahan serta bagaimana konsep preservasi dan revitalisasi dalam mempertahankan objek wisata. Penelitian ini menggunakan metode campuran/kombinasi pendekatan kuantitatif dan kualitatif (mix methods). Teknik pengumpulan data menggunakan wawancara mendalam, angket, observasi, studi dokumentasi, studi pustaka dan penelusuran data daring. Sumber data primer diperoleh langsung dari observasi dan wawancara langsung yang terdiri dari pihak pemerintah dan swasta (stakeholders), serta penyebaran angket menggunakan Google Form kepada 100 responden dengan teknik purposive sampling dan berdasarkan kunjungan wisatawan yang pernah berkunjung ke kawasan Danau Toba berdasarkan daya tarik kunjungan, kondisi kebersihan, jaminan keamanan, kepuasan terhadap pelayanan pengelola, kepuasan terhadap objek wisata, kepuasan selama berwisata. Hasil penelitian menunjukkan bahwa respon wisatawan terhadap kualitas objek wisata Rumah Adat masih memiliki nilai presentase yang tinggi yaitu 60,8% dan diikuti dengan tingkat kepuasan dalam berwisata sebesar 45,7%. Namun, poin kebersihan masih memiliki presentase yang rendah yaitu 20,6 yang berarti pentingnya peningkatan kebersihan di kawasan wisata yang terletak di kawasan Danau Toba Samosir tersebut. Perhatian dan kerjasama yang baik dari pemerintah daerah hingga pihak swasta sangat penting untuk menjaga dan melestarikan bangunan sehingga tercipta kenyamanan bagi wisatawan yang berkunjung, serta kesadaran wisata yang sangat perlu ditingkatkan untuk mendukung kemajuan di kawasan wisata Danau Toba. Peran serta masyarakat juga sangat dibutuhkan dalam pengembangan objek wisata rumah adat agar tidak punah namun kawasan ini semakin menunjukkan jati dirinya dalam pelestarian dan revitalisasinya.Kata Kunci: Rumah Adat Batak; Daya Tarik; Kunjungan Wisatawan; Revitalisasi; Danau Toba